2011
DOI: 10.1007/s12562-011-0352-9
|View full text |Cite
|
Sign up to set email alerts
|

The functional effect of Gly209 and Ile213 substitutions on lysozyme activity of family 19 chitinase encoded by cyanophage Ma-LMM01

Abstract: ORF69 in the cyanophage infecting Microcystis aeruginosa, Ma-LMM01, shows homology to the family 19 chitinases where the catalytic domain has structural similarity to lysozyme. Chitinases hydrolyze chitin, a b-1, 4-linked monopolymer of N-acetylglucosamine (GlcNAc); whereas lysozymes hydrolyzes peptidoglycan, alternating b-1, 4-linked copolymers of N-acetylmuramic acid (MurNAc) and GlcNAc. Using amino acid sequence comparison to ORF69, the putative sugar binding residues, Gln162 and Lys165, from the barley chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Two proteins, WP_143898266.1 assigned as C25GH19A and WP_161664743.1 assigned as C25GH19B, were annotated as glycoside hydrolase 19 (GH19) family hydrolases. The GH19 family includes chitinases derived from bacteria and plants, and lysozymes or endolysins derived virus Ma-LMM01 (Hosoda et al 2011) and the endolysin (AEX26904.1) derived from Salmonella phage SPN1S (Park et al 2014) is 54% and 31%, respectively. According to the multiple sequence alignment (Fig.…”
Section: Mining the Bacteriolytic Enzymes Of C25j21mentioning
confidence: 99%
“…Two proteins, WP_143898266.1 assigned as C25GH19A and WP_161664743.1 assigned as C25GH19B, were annotated as glycoside hydrolase 19 (GH19) family hydrolases. The GH19 family includes chitinases derived from bacteria and plants, and lysozymes or endolysins derived virus Ma-LMM01 (Hosoda et al 2011) and the endolysin (AEX26904.1) derived from Salmonella phage SPN1S (Park et al 2014) is 54% and 31%, respectively. According to the multiple sequence alignment (Fig.…”
Section: Mining the Bacteriolytic Enzymes Of C25j21mentioning
confidence: 99%
“…Besides, a number of papers [ 20 , 21 ] pointed out that some GH19 proteins are coded by single genes or modular multi-domain lytic gene cassettes in bacteriophages or prophages. A few of these enzymes have been biochemically characterized and classified as endolysins with lysozyme-like properties [ 22 , 23 , 24 , 25 , 26 , 27 ]. Endolysins are produced in the late phases of the bacteriophage’s lytic cycle and attack the peptidoglycan polymer of the host cell wall, thus allowing for the release of the phage progeny.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that some chitinases from diverse sources, besides being able to cleave the O-glycosidic bonds in chitin chains, also have lysozyme activity. 25,26,27 Hevamine, a GH18 chitinase firstly purified from the latex of Hevea brasiliensis, is probably the better known chitinase with lysozyme activity. 28,29 Most bacterial cells are encased by a cell wall constituted mainly by a mesh-like layer of peptidoglycan (PG), also known as murein, which guarantees cell integrity and shape.…”
Section: Discussionmentioning
confidence: 99%